KARAKTERISTIK ARAH DAN TINGGI GELOMBANG SIGNIFIKAN DI LAUT SULAWESI - Godwin Parulian Tindaon; Rignolda Djamaluddin; Hermanto W.K. Manengkey; Edwin L.A. Ngangi (Sam Ratulangi University, 2022)
The Celebes Sea is an important area in terms of utilization of coastal and sea space. This study aims to describe the direction characteristics and significant wave heights in several areas of the Celebes Sea in various seasons and to analyze the characteristics of daily and monthly waves. The wave data used in this study is the result of Wavewatch-III wave predictions with a wave data duration of 2 years, January 2020 - December 2021. The areas that are the observation area are Station 1 (3°N 121°E), Station 2 (3° N 123° E), and Station 3 (3° N 125° E). Through the spatial-temporal analysis method, the results are presented in the form of a rose graph of the direction of the incoming wave. The most wave propagation directions that occur at the three coordinate points (Stations) for 2020 to 2021 come from the North and Northeast. The proportion of significant wave height above 1 meter indicates that the largest waves proportion has been in 2020 at the beginning of the year while in 2021 at the end of the year. Significant wave heights in 2020 occurred most strongly in the North season at the beginning of the year while in 2021 the strongest significant wave heights occurred in the North season at the end of the year. Besides the proportion of significant wave height occurrences in the South season, especially May and July in 2021. Analysis of daily waves at the overall measurement time shows that the direction of propagation of the waves has no difference based on different years. Daily significant wave heights above 2 meters have a tendency to occur in the morning to evening in 2020. Keywords: Waves, Wavewatch-III, Celebes Sea ABSTRAK Laut Sulawesi merupakan kawasan penting dalam hal pemanfaatan ruang pantai dan laut. Penelitian ini bertujuan untuk mendeskripsikan karakteristik arah, dan tinggi gelombang signifikan di beberapa kawasan Laut Sulawesi dalam berbagai musim yang berlangsung serta menganalisis karakteristik gelombang harian dan bulanan. Data gelombang yang digunakan dalam penelitian ini merupakan hasil prediksi gelombang Wavewatch-III dengan durasi waktu data gelombang 2 tahun, Januari 2020 - Desember 2021. Daerah yang menjadi area pengamatan yaitu Stasiun 1 (3°LU 121°BT), Stasiun 2 (3°LU 123° BT), dan Stasiun 3 (3°LU 125° BT). Melalui metode analisis spasial-emporal hasilnya disajikan dalam bentuk grafik mawar arah datang gelombang. Arah rambat gelombang terbanyak yang terjadi di ketiga titik koordinat (Stasiun) untuk tahun 2020 sampai 2021 datang dari arah Utara dan Timur Laut. Proporsi tinggi gelombang signifikan di atas 1 meter menunjukkan tahun 2020 paling besar proporsinya pada awal tahun sementara pada tahun 2021 pada akhir tahun. Tinggi gelombang signifikan pada tahun 2020 terjadi paling kuat pada musim Utara awal tahun sementara pada tahun 2021 tinggi gelombang signifikan paling kuat terjadi pada musim Utara akhir tahun disamping proporsi kejadian tinggi gelombang signifikan pada musim Selatan khususnya Mei dan Juli di tahun 2021. Analisis gelombang harian pada keseluruhan waktu pengukuran menunjukkan bahwa arah rambat gelombang tidak memiliki perbedaan berdasarkan tahun yang berbeda. Tinggi gelombang signifikan harian di atas 2 meter memiliki kecenderungan terjadi pada pagi sampai sore hari pada tahun 2020. Kata Kunci: Gelombang, Wavewatch-III, Laut Sulawesi